THE THIRD, MOLECULAR, FORM OF CARBON: FULLERENES, CARBON NANOTUBES AND ONIONS SOME PHYSICAL PROPERTIES OF FULLERITES - Zubov, V. L. (2004)
A brief review is presented of the pre-history and discovery of fullerenes (and then carbon nanotubes) that make the third molecular form of carbon, and of various, predominantly physical, properties of fullerites, i.e. of crystals composed of fullerene molecules. Particular attention is being given to the intermolecular forces, especially at orientationally disordered phases. The Girifalco potential is presented for eight ful\erenes from CJx to C96 and its generalization is made for the interactions between'the different fullerene molecules, Cm and c•. The thermodynamic properties of the high-temperature modifications of a family of the fullerites, from C36 UP.. to the C96, calculated in equilibrium with their saturated vapors on the basis of the correlative method of the unsymmetrized self-consistent field that enables one to take into account the strong anharmonicity of the lattice vibrations, are discussed. The calculations were accomplished up to the temperature of loss of stability (spinodal point) Ts. We compare our results with available experimental data. The behavior of sorne characteristics is considered in their dependence on the number of atoms in the molecule. Using the Lindemann's melting criterion we estimate a possible melting curve for the C611 fullerite.